METODE MEMAHAMI NAá¹¢-NAá¹¢ TEOLOGIS: Studi tentang Wacana Inklusif Ahl al-KitÄb - Sakhok, Jazilus (Jurnal THEOLOGIA, 2016)
This paper examined how to understand the texts of the Qur'an andÂ á¸¤adÄ«th concerning the concept of Ahl al-KitÄb. The concept of the Ahl al-KitÄb becomes frequently debatable for there have been contradictions of the texts with other texts. To avoid contradictory understanding, it can be reached by way of compromising various existing texts. Through this method, it reveals that there is no contradictory theological understanding in the Qur'an and á¸¤adÄ«th about how Muslims should behave towards and treat Ahl al-KitÄb. From the texts it precisely shows an understanding that Muslims have to give respect, to recommend for doing good, and to acknowledge the existence of the Ahl al-KitÄb as long as each of them does not meddle in the affairs of each faith. The texts also produce a strong message that alludes to an inclusive teaching of Islam towards Ahl al-KitÄb.Tulisan ini mengkaji tentang cara memahami nash-nash al-Qurâ€™an danÂ Hadis mengenai konsep Ahl al-KitÄb. Konsep Ahl al-KitÄb selalu menjadiÂ perÂÂÂdebatan karena seolah-olah telah terjadi kontradiksi di antara satu naá¹£ denganÂ nash yang lainnya. Untuk menghindari pemahaman yang kontradiktif, bisaÂ ditempuh dengan cara mengkompromikan dan menjamaâ€™kan berbagai naá¹£ yangÂ ada. Melalui metode tersebut ternyata tidak ditemukan kontradiksi pemahamanÂ secara teologis di dalam al-Qurâ€™an dan Hadis mengenai bagaimana seharusnyaÂ umat Islam bersikap terhadapÂ  Ahl al-KitÄb. Dari naá¹£-naá¹£ itu justeru meÂnunjukÂkan satu pemahaman supaya memberikan respek, menganjurkan berbuat baik, dan mengakui eksistensi Ahl al-KitÄb yang harus dihormati, selama tidak saling menÂcampuri urusan keimanan masing-masing. Naá¹£-naá¹£ tersebut juga mengÂhasilkan pesan kuat akan sikap inklusif ajaran Islam terhadap Ahl al-Kitab.